Problems and Challenges of Suku Anak Dalam in the 2019 General Election: A Policy Recommendation - Hertanto, Hertanto; Maryanah, Tabah; Warganegara, Arizka (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
In a democracy, the state is obligated to guarantee citizens’ political rights, particularly the right to vote and to run (and be elected) in any general election. However, case studies in four districts of Jambi Province (Batanghari, Sarolangun, Tebo, and Merangin) reveal the opposite. Many members of the Suku Anak Dalam (SAD) community were excluded from the permanent voter list, effectively depriving them of their constitutional right to vote. This study investigates what causes this exclusion and offers relevant policy recommendations. The interviews with key informants identified several underlying causes in the 2019 elections: the absence of identity cards, low levels of literacy and education, poor economic conditions, and various technical obstacles. Other barriers included the lack of special polling stations and non-inclusive voting procedures. These findings suggest the need to strengthen education and literacy programs and establish accessible polling stations, as well as more inclusive voting procedures for the SAD community.